Green self-accountability and temporal distance impact on sustainable consumption behavior: the mediating role of anticipated emotions - Zhong, Bowei; Feng, Xingwang; Li, Xiaogang; Fan, Wei (Frontiers in Psychology, 2025)
PurposeWith the rise in global consumption depleting natural resources and harming the environment, promoting sustainable consumption is essential. Our study explores how green self-accountability affects sustainable purchasing over different time frames, examining the impact on short (one week) and long-term (one year) choices toward green products and the underlying mechanisms.MethodsWe conducted two experiments where participants made green purchasing decisions, with the first activating green self-accountability and the second also measuring anticipated emotional responses.ResultsFindings show that green self-accountability boosts sustainable purchasing, particularly for immediate choices, driven by anticipated pride in buying green products.ConclusionGreen self-accountability significantly enhances sustainable purchasing, aided by anticipated pride. This suggests that marketing strategies emphasizing environmental urgency and consumers’ eco-unfriendly behaviors can foster sustainable consumer habits.